Análise de multicritérios e simulação de uso e cobertura da terra na área de entorno da UHE Itutinga: um subsídio ao planejamento ambiental - Douglas Felipe Lucas (2021)
Due to the high potential of hydraulic use in Brazil, most of the national electric energy comes from hydroelectric plants. However, their implementation and operation can cause damage to the environment. Given this scenario, the presentation of the Environmental Plan for the Conservation and Use of the Artificial Reservoir Surroundings (PACUERA) is now required in the licensing of hydroelectric plants. It can be defined as a set of guidelines and proposals with the objective of disciplining conservation, recovery, use and occupation of the surroundings of the artificial reservoir, based on socio-environmental diagnosis and zoning. One of the subsidies for the delimitation of socio-environmental zoning is the detection and prediction of changes in land use and occupation. The objective of this research is to build a predictive model of change for the year 2030 and simulate two hypothetical scenarios: one without considering the usage guidelines present in the PACUERA socio-environmental zoning and other assuming the implementation of the guidelines. It will also be evaluated the potential for anthropization and preservation of the area and its conflict of interest. For this purpose, multicriteria analyzsis were used with the Weighted Sum method to identify the potential for expansion of human activities and potential for environmental preservation, and the Combinatorial Analysis method to assess conflicts of interest. To simulate land use and land cover for the year 2030, the Land Change Modeler – LCM module that composes the IDRISI Selva software version was used. In estimating the amount of changes, the land use and land cover maps for the years 2007 and 2018 were employed as input data and the calculation of transition rates based on Markov Chains was undertaken. Similarity weighted instance-based learning (SimWeight) was applied to calculate the transition potentials of terrain changes, considering the influence of a set of spatial explanatory variables. The model results reveal a trend of growth in agricultural activities and urban expansion at the expense of grazing areas and native natural vegetation. The simulated hypothetical scenarios demonstrated that the adoption of PACUERA's socio-environmental zoning disciplines changes in land use and coverage classes, supporting a more sustainable environment in the surroundings of the Itutinga HPP. As practical implications, these results demonstrate that the implementation of PACUERA's socio-environmental zoning can reconcile the various interests in relation to the use of water and soil around the reservoir, in order to avoid environmental degradation and maximize socioeconomic benefits arising from the enterprise. The research developed in this dissertation is original and combines, in a logical and structured way, key concepts of modeling environmental systems. The work contributes as a subsidy to environmental planning by explaining the methodological framework for the protection, recovery and promotion of the sustainable use of terrestrial ecosystems, in order to stop the loss of biodiversity.